2016
DOI: 10.1016/j.diff.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Complex epithelial remodeling underlie the fusion event in early fetal development of the human penile urethra

Abstract: We recently described a two-step process of urethral plate canalization and urethral fold fusion to form the human penile urethra. Canalization (“opening zipper”) opens the solid urethral plate into a groove, and fusion (“closing zipper”) closes the urethral groove to form the penile urethra. We hypothesize that failure of canalization and/or fusion during human urethral formation can lead to hypospadias. Herein, we use scanning electron microscopy (SEM) and analysis of transverse serial sections to better cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 22 publications
3
52
0
Order By: Relevance
“…Recent work from our group using optical projection tomography (OPT) challenged prior dogma regarding mechanisms of development of the human penile urethra and analogous structures in the clitoris. We demonstrated that two sequential distal canalization and proximal fusion processes are involved rather than a single fusion process of paired urethral folds (Li et al, 2015;Shen et al, 2016). Prior to our use of 3D reconstruction, this Despite these advances, differential protein localization within developing human urogenital organs remains poorly characterized in three dimensions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent work from our group using optical projection tomography (OPT) challenged prior dogma regarding mechanisms of development of the human penile urethra and analogous structures in the clitoris. We demonstrated that two sequential distal canalization and proximal fusion processes are involved rather than a single fusion process of paired urethral folds (Li et al, 2015;Shen et al, 2016). Prior to our use of 3D reconstruction, this Despite these advances, differential protein localization within developing human urogenital organs remains poorly characterized in three dimensions.…”
Section: Discussionmentioning
confidence: 98%
“…3). This is followed by the subsequent fusion of multiple interlacing ventral epithelial "cords" to form the mature tubular penile urethra (Li et al, 2015;Shen et al, 2016). As described prior, SPIM has since supplanted the use of OPT in our laboratory (Isaacson et al, 2018a).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The urethra in the penile shaft forms via distal canalization of a solid urethral plate to form a wide-open urethral groove, followed by proximal to distal fusion of the urethral folds, a process far more complicated than originally envisioned [64]. This results in formation of the tubular penile urethra and superficial midline penile raphe.…”
Section: Discussionmentioning
confidence: 99%
“…However, in mice and rats the urethral plate does not extend into the distal aspect of the developing penis (Hynes and Fraher, 2004a, b;Sinclair et al, 2016bSinclair et al, , 2016aKluth et al, 2011), and thus a different morphogenetic mechanism is utilized to generate the distal aspect of the penile urethra in mice. In the developing human penis, the urethral plate canalizes to form a widely open urethral groove, whose edges (urethral folds) fuse in the ventral midline to form the tubular penile urethra (Li et al, 2015b;Shen et al, 2016). In mice a ventral groove (the preputial-urethral groove) forms in the distal aspect of the developing mouse penis independent of and distal to the urethral plate.…”
Section: Introductionmentioning
confidence: 99%